PERANCANGAN SISTEM KEUANGAN DI PUSKESMAS KARANGAWEN II DEMAK - Subroto, Vivi Kumalasari; Endaryati, Eni (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
In connection with the need for a financial information system, the Karangawen II Demak Community Health Center is a research object that requires such an information system. This is because in carrying out its operational activities, the Karangawen II Demak Community Health Center has not used an adequate financial information system so that track records of income receipts, shopping expenditures and financial balances have not been recorded properly. This of course has an impact on the smooth operational activities of the Karangawen II Demak Health Center and also has an impact on the assessment of current assets owned by the Karangawen II Demak Health Center. To overcome this problem, this financial information system will be developed on a web basis so that it is hoped that it can help the operational activities of the health center.